Development of a Web-Based Student Complaint System with Activity Dashboard - Pratama, Wildan Dwi; Widiono, Suyud (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study develops a web-based student complaint information system designed to overcome the limitations of manual reporting processes commonly used in schools. Manual complaint handling often causes delays in responses, difficulty in tracking reports, and the absence of structured monitoring of user activities. To address these problems, the system integrates multi-user roles consisting of administrators, officers, and students, as well as an activity statistics dashboard that visually presents complaint data. The system was developed using the Waterfall method through stages of requirement analysis, system design, implementation, and testing. The features include complaint category management, user management, login history recording, and visualization of the number of complaints, comments, and responses. The implementation results show that the system effectively accelerates report submission, simplifies monitoring for officers, and helps administrators conduct structured evaluations using interactive statistical displays. Testing indicates that all functions operate properly and support efficient communication in the complaint handling workflow. Overall, this system provides a more organized, transparent, and data-driven solution for managing student complaints in schools